(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
This article provides a history of the implementation, in the United States and Europe, of collection processes on cinema attendance, on the results obtained by films in terms of admissions or box-office receipts, and on the international trade of films. The contribution shows how the US industry was already from the 1910s concerned with obtaining a statistical portrait of European markets while efforts to set up an integrated European statistical tool, imagined in the 1920s, did not come to fruition. This was only achieved in the 1990s with the creation of the European Audiovisual Observatory and its LUMIERE database.